Pengaruh Perilaku Diet Dengan Kacang Merah dalam Penurunan Berat Badan Remaja Putri - Suci Munawaroh (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2023)
Problems weight and self-appearance cause teenagers to have a great interest in getting the weight they want. One of the foods that can be consumed while on a diet is red beans. The purpose of the study was to determine the effect of dietary behavior with red beans in weight loss for adolescent girls. This research method is a quasi-experimental/quasi-experimental research with a quantitative approach. The population of this study is all young women who have an interest in losing weight. The sampling technique was purposive sampling. The inclusion criteria for this study were female adolescents aged 15-18 years with a Body Mass Index (BMI) > 25. The research data was collected using a questionnaire with google form. Researchers used 20 respondents as a sample. The data obtained, the average weight of adolescent girls before the diet was 56.85 kg and the average weight of the adolescent girls after the diet was 49.55 kg. The behavior of the red bean diet shows 80% of the appropriate diet behavior and 20% are in the inappropriate category. These data indicate that consuming red beans can lose weight, but the decrease is not too significant.